Delignifikasi Batang Kayu Sengon oleh Trametes versicolor - Azmi Azhari; Syamsul Falah; Laita Nurjannah; Suryani Suryani; Maria Bintang (IPB University, 2014)
Delignification is a lignin degradation, a preliminary process in industries that used cellulose containing substrates. Sengon logs are often used for the material in pulp industry because it has high levels of cellulose and low level of lignin. The aim of this study was delignification of sengon logs by using T.versicolor. The methods used include observation growth of T.versicolor compared with Phanerochaete chrysosporium, the rate of of lignin degradation (black liquor), delignification of sengon logs using T.versicolor and the chemical assay of sengon logs before and after delignification. The results of this study showed that delignification by T.versicolor was faster compared to P.chrysosporium based on the rate of lignin degradation (black liquor). The result showed that delignification by T.versicolor at room temperature reduced lignin of sengon logs by 37.31% within 20 days. Chemical assay performed on delignified sengon wood showed decreased level of ethanol benzene, soluble extractive substances, holocellulose, and cellulose and an increase of hemicellulose level.